Aetiopathogenesis of caprine q-fever in Kedah and Penang, Malaysia - Lokman, Norina (2011)
Q fever is a worldwide zoonosis of public health concern and is prevalent in most places of the world except New Zealand and Antartica. The etiological agent named Coxiella burnetii is an obligate, gram variable and intracellular pathogen that cannot be grown in axenic medium. The genome size varies from 1·5 to 2·4 Mb. The majority of natural C. burnetii infections are the result of inhalation of contaminated aerosols. C. burnetii infection is usually asymptomatic with spontaneous recovery. Predominant clinical manifestations are fever, pneumonia and granulomatous hepatitis for acute cases and endocarditis for chronic cases. Infection in animals is mainly subclinical but has been associated with late abortions, stillbirth, delivery of weak offspring and also infertility. Abortions during Q fever epizootics have been described in goats and sheep but abortion in dairy cows is rare, although reproductive disorders and mastitis can occur.Rapid diagnosis of the etiological agent of caprine abortion in Malaysia is of great importance in terms of control and prevention. Diagnosis of Q fever in Malaysia is usually based on the detection of specific antibodies in the adult population by ELISA tests. A total of 2266 sera from 108 goat farms were taken for surveillance which involved six states located in the northern and middle zones in Peninsular Malaysia. The finding revealed that C.burnetii is widespread in goats in Peninsular Malaysia. Furthermore, there is no breed predilection as far as Q fever is concerned. The risk analysis showed that female goats is prone to a higher risk of acquiring Q fever (95%CI, 1.064 – 1.206). It is believed that sex hormone play a role in pathogenesis of Q fever infection. Age also appears to be a risk factor for Q fever. Goats less than 2 years old is one time risky compared to that of > 2-year-old (1.13 95%CI, 0.677 – 1.89). High hemoglobin level, leukocytosis and thrombocytosis are indicative of Q fever infection in goats. C. burnetii is shed in amniotic fluid, placenta, manure, urine and milk which posses high risk to other animal as well as human. 150 carcasses from 5 infected goat farms in northern zone that were autopsied and the result revealed necrotic placentitis with diffused white foci with creamy exudates at the edges of the cotyledons and in the intercotyledonary areas. Diagnosis relies upon impression smear and histopathological examination. Morphological changes of necrotic placentitis,interstitial pneumonia, hepatitis and nephritis were seen in majority of cases. These lesions were suggestive of acute Q-fever. Acute cases yielded lesions conforming to doughnut granuloma while those of the chronic form exhibited chronic inflammation. Out of the total suspected cases, 152 (77.2%) were confirmed as positive of Q-fever based on immunohistochemistry (IHC). Thus, this study demonstrated pertinent lesions of acute and chronic forms of Q-fever which may be beneficial to laboratories without IHC facilities. Thirty placentas and umbilical cords of two fetuseswhich were stained with Giemsa and Machiavello (MAC) stains revealed hazy bluish structures within the cytoplasm of trophoblasts that contained small, red coccobacilli organism. The placenta’s inoculum inoculated into 7-day-old SPF eggs appeared to show cloudy chorion with small spotted white foci attached to the chorionic membrane, collapsed blood vessels and the whole fetus showed hemorrhages with opacity of both eyes. Harvested yolk sac at different dilution that were stained with Machiavello and Gimenez stains showed the present of numerous red coccobacilli attached to the yolk sac, suggestive of C. burnetii. All six tissues (100%) revealed positive immunohistochemistry (IHC) when brownish color appears on green background tissue. Four PET samples (placenta tissue) of goats collected from 2007 and 2008, three fresh tissues and four out of ten vaginal samples of aborted does, were positive for Coxiella burnetiiat 687-bp using PCR. The methods developed in this study provide a basis for a more comprehensive understanding of the evolution of Q fever that will hopefully pace for the development of improved epidemiological and diagnostic tools that will contribute to the success of the disease control programmes in Malaysia.